Toxoplasma-induced behavior changes - is microbial dysbiosis the missing link? - Prandovszky, Emese; Severance, Emily G.; Splan, Victor W.; Liu, Hua; Xiao, Jianchun; Yolken, Robert H. (Frontiers in Cellular and Infection Microbiology, 2024)
Toxoplasma gondii (T. gondii) is one of the most successful intracellular protozoa in that it can infect the majority of mammalian cell types during the acute phase of infection. Furthermore, it is able to establish a chronic infection for the host’s entire lifespan by developing an encysted parasite form, primarily in the muscles and brain of the host, to avoid the host immune system. The infection affects one third of the world population and poses an increased risk for people with a suppressed immune system. Despite the dormant characteristics of chronic T. gondii infection, there is much evidence suggesting that this infection leads to specific behavior changes in both humans and rodents. Although numerous hypotheses have been put forth, the exact mechanisms underlying these behavior changes have yet to be understood. In recent years, several studies revealed a strong connection between the gut microbiome and the different organ systems that are affected in T. gondii infection. While it is widely studied and accepted that acute T. gondii infection can lead to a dramatic disruption of the host’s normal, well-balanced microbial ecosystem (microbial dysbiosis), changes in the gut microbiome during the chronic stage of infection has not been well characterized. This review is intended to briefly inspect the different hypotheses that attempt to explain the behavior changes during T. gondii infection. Furthermore, this review proposes to consider the potential link between gut microbial dysbiosis, and behavior changes in T. gondii infection as a novel way to describe the underlying mechanism.